The effect of holdings data frequency on conclusions about mutual fund behavior - Elton, Edwin J.; Gruber, Martin J.; Blake, Christopher R.; Krasny, Yoel; Ozelge, Sadi O. (Journal of Banking & Finance, 2010)
A number of articles in financial economics have used quarterly or semi-annual mutual fund holdings data to test hypotheses about investment manager behavior. This article reexamines four well-known hypotheses in finance to determine whether the results of prior tests of these hypotheses remain valid when higher frequency (monthly) holdings data are employed. The areas examined are: momentum trading, tax-motivated trading, window dressing, and tournament behavior. We find that the use of monthly holdings data rather than quarterly holdings data or, in the case of tournament behavior, holdings data rather than monthly return data, change, and in some cases reverse, previous results. This occurs because monthly holdings data capture a large number of trades missed by quarterly data (18.5% of the trades) and permit a more precise estimation of the timing of trades.